Biodiversity of the metazoan parasites of Hoplias malabaricus (Bloch, 1794) from the Jacaré-Pepira River, Tietê-Jacaré River Basin, São Paulo State, Brazil - Bueno, Regiane Maria Dos Reis [UNESP]; Leite, Lucas Aparecido Rosa [UNESP]; Pelegrini, Larissa Sbeghen; Abdallah, Vanessa Doro; Azevedo, Rodney Kozlowiski de (Boletim do Instituto de Pesca, 2022)
We recorded the parasitic fauna of Hoplias malabaricus in a Neotropical River from southeastern Brazil, the Jacaré-Pepira River, in the Tietê-Batalha River Basin. The objective of this study was to inventory the composition of the parasitic fauna of H. malabaricus collected, through ecological and biodiversity approaches. A total of 30 specimens of H. malabaricus were collected in 2018 using fishing nets. Parasites were prevalent in 96.6% of the hosts, with 710 parasites specimens collected, divided into 22 species from 4 different taxa (i.e., Monogenea, Digenea, Nematoda, and Acanthocephala). This was the first survey about the parasitic fauna of H. malabaricus in this river, where three species are new records for this host (i.e., Gussevia sp. 1, Gussevia sp. 2, and Raphidascaris sp.). All species found are new records for the Jacaré-Pepira River, which together with all the data obtained in the study, collaborates to increase knowledge and understanding of the global fish parasite biodiversity.
Biodiversidade dos metazoários parasitos de Hoplias malabaricus (Bloch, 1794) do Rio Jacaré-Pepira, Na Bacia Do Rio Tietê-Jacaré, Estado de São Paulo, Brasil
Keywords: Fish parasitology; Parasitic biodiversity; Parasitic ecology; Species inventory